HIDROPONIK SEDERHANA SEBAGAI ALTERNATIF PENGHIJAUAN DI LINGKUNGAN SEKOLAH (STUDI PADA LINGKUNGAN SEKOLAH TK NURUL I’TISHOM, BINTARA, BEKASI) - Abdul Chalim; RL Pangaribowo; Ida Bagus Rabindra; Lailatus Siami (Universitas Trisakti, 2021)
Community Service in the form of Counseling on the Empowerment of Kindergarten Teachers in the reforestation of school land has been carried out at Nurul I'tishom Kindergarten Kel. Bintara, Kec. Bekasi Barat on Friday, January 29, 2021. Community Service in the form of Counseling on the Empowerment of Kindergarten Teachers in The reforestation of school land has been carried out at Nurul I'tishom Kindergarten Kel. Bintara, Kec. Bekasi Barat on Friday, January 29, 2021. The background of this program is carried out with the aim of the desire of the partners to carry out reforestation which is constrained by the limitations of the remaining outdoor space in the school environment.The hydroponic planting system is an alternative to reforestation on limited land. Extension materials are provided online, consisting of hydroponic planting systems and Hydroponic Plant Arrangement Design. Participants in the activity are teachers, education staff, parents of students and the surrounding community. This activity received a good response as evidenced by the large number of participants and enthusiastic participants in the discussion and question and answer session. From the partners, there is a suggestion that there be further activities in the form of training with a longer number of face-to-face hours. The methods used in the implementation are counseling, demonstration and training